Polyporus Umbellatus Protects Against Renal Fibrosis by Regulating Intrarenal Fatty Acyl Metabolites - Wang, Yan-Ni; Wu, Xia-Qing; Zhang, Dan-Dan; Hu, He-He; Liu, Jian-Ling; Vaziri, Nosratola D.; Guo, Yan; Zhao, Ying-Yong; Miao, Hua (Frontiers in Pharmacology, 2021)
Background: Chronic renal failure (CRF) results in significant dyslipidemia and profound changes in lipid metabolism. Polyporus umbellatus (PPU) has been shown to prevent kidney injury and subsequent kidney fibrosis. Methods: Lipidomic analysis was performed to explore the intrarenal profile of lipid metabolites and further investigate the effect of PPU and its main bioactive component, ergone, on disorders of lipid metabolism in rats induced by adenine. Univariate and multivariate statistical analyses were performed for choosing intrarenal differential lipid species in CRF rats and the intervening effect of n-hexane extract of PPU and ergone on CRF rats. Results: Compared with control group, decreased creatinine clearance rate indicated declining kidney function in CRF group. Based on the lipidomics, we identified 65 lipid species that showed significant differences between CRF and control groups. The levels of 12 lipid species, especially fatty acyl lipids including docosahexaenoic acid, docosapentaenoic acid (22n-3), 10,11-Dihydro-12R-hydroxy-leukotriene C4, 3-hydroxydodecanoyl carnitine, eicosapentaenoic acid, hypogeic acid and 3-hydroxypentadecanoic acid had a strong linear correlation with creatinine clearance rate, which indicated these lipid species were associated with impaired renal function. In addition, receiver operating characteristics analysis showed that 12 lipid species had high area under the curve values with high sensitivity and specificity for differentiating CRF group from control group. These changes are related to the perturbation of fatty acyl metabolism. Treatment with PPU and ergone improved the impaired kidney function and mitigated renal fibrosis. Both chemometrics and cluster analyses showed that rats treated by PPU and ergone could be separated from CRF rats by using 12 lipid species. Intriguingly, PPU treatment could restore the levels of 12 lipid species, while treatment with ergone could only reverse the changes of six fatty acids in CRF rats. Conclusion: Altered intrarenal fatty acyl metabolites were implicated in pathogenesis of renal fibrosis. PPU and ergone administration alleviated renal fibrosis and partially improved fatty acyl metabolism. These findings suggest that PPU exerted its renoprotective effect by regulating fatty acyl metabolism as a potential biochemical mechanism. Therefore, these findings indicated that fatty acyl metabolism played an important role in renal fibrosis and could be considered as an effective therapeutic avenue against renal fibrosis.